2016
DOI: 10.1097/aud.0000000000000334
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Priming in Children with Hearing Loss: Effect of Speech Mode, Fidelity, and Lexical Status

Abstract: Objectives Our research determined 1) how phonological priming of picture naming was affected by the mode (auditory-visual [AV] vs auditory), fidelity (intact vs non-intact auditory onsets), and lexical status (words vs nonwords) of speech stimuli in children with prelingual sensorineural hearing impairment (CHI) vs. children with normal hearing (CNH); and 2) how the degree of hearing impairment (HI), auditory word recognition, and age influenced results in CHI. Note that some of our AV stimuli were not the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
4
1
Order By: Relevance
“…Contrary to the findings of this study, Jerger et al (2016) concluded that children with hearing loss responded similarly to phonological primes as compared to children with typical hearing. Differences in findings may be related to methodological differences between these studies.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrary to the findings of this study, Jerger et al (2016) concluded that children with hearing loss responded similarly to phonological primes as compared to children with typical hearing. Differences in findings may be related to methodological differences between these studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Differences in findings may be related to methodological differences between these studies. The Jerger et al (2016) study included participants with a range of hearing losses (and consequently, who wore a range of devices) who were between the ages of 4 and 15 years. The present study evaluated only children with cochlear implants between the ages of 5 and 7 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations